2017
DOI: 10.18632/oncotarget.19584
|View full text |Cite
|
Sign up to set email alerts
|

Facile total synthesis of lysicamine and the anticancer activities of the RuII, RhIII, MnII and ZnII complexes of lysicamine

Abstract: Lysicamine is a natural oxoaporphine alkaloid, which isolated from traditional Chinese medicine (TCM) herbs and has been shown to possess cytotoxicity to hepatocarcinoma cell lines. Reports on its antitumor activity are scarce because lysicamine occurs in plants at a low content. In this work, we demonstrate a facile concise total synthesis of lysicamine from simple raw materials under mild reaction conditions, and the preparation of the Ru(II), Rh(III), Mn(II) and Zn(II) complexes 1–4 of lysicamine (LY). All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Additional studies have shown that metallodrugs can target CDKs and cycle proteins to block the cell cycle in different phases. For instance, Ru(II), Rh(III), Mn(II), and Zn(II) complexes blocked the cell cycle in the S-phase, thus inhibiting cell proliferation by reducing the levels of cyclins A2/B1/D1/E1, CDK-2/6, and PCNA and increasing the levels of p21, p27, p53, and CDC25A [ 121 ].…”
Section: Ru(ii) Complexesmentioning
confidence: 99%
“…Additional studies have shown that metallodrugs can target CDKs and cycle proteins to block the cell cycle in different phases. For instance, Ru(II), Rh(III), Mn(II), and Zn(II) complexes blocked the cell cycle in the S-phase, thus inhibiting cell proliferation by reducing the levels of cyclins A2/B1/D1/E1, CDK-2/6, and PCNA and increasing the levels of p21, p27, p53, and CDC25A [ 121 ].…”
Section: Ru(ii) Complexesmentioning
confidence: 99%
“…An oxoaporphine alkaloid, lysicamine isolated from Asimina triloba inhibited the growth of hepatoma HepG2 and lung cancer NCI-H460 cells. Lysicamine induced S-phase arrest via down-regulation of the expression of cyclin A2/B1/D1/E1 and CDK2/6 [120]. FLT3, a type III receptor tyrosine kinase acts as a proto-oncogene involved in crucial steps of haematopoiesis such as proliferation, differentiation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Chen and Liang (2010) reported the anticancer activity of metal complex of liriodenine, oxoglaucine and oxoisoaporphine, as more potent to corresponding ligands. Furthermore, Qin et al., (2017) synthesized four metal complexes of lysicamine, that is, [Ru(LY)Cl 2 (DMSO) 2 ]·3H 2 O, [Rh(LY‐OH)Cl 3 CH 3 OH], [Mn(LY) 3 ](ClO 4 ) 2 .3CHCl 3 , and [Zn(LY) 2 (ClO 4 ) 2 ], and reported their cytotoxicity against HepG2 and NCI‐H460 cell lines. Rh and Mn‐metal complex of lysicamine ( 26 ) exhibited higher cytotoxicity against HepG2 and NCI‐H460 (Figure 20).…”
Section: Caspase‐3 Activatorsmentioning
confidence: 99%